Evaluation of junior courses students' level of mobilization of functional backlogs at the dosed physical activities at the pedagogical university - A.I. Bosenco; I.I. Samokih; S.V. Strashko; N.A. Orlik; E.P. Petrovsky (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
A study of the functional capacity of the organism lower division students. The study involved 85 students of 1-2 courses, 14 of which were engaged and were part of the team of the University of volleyball. As a student of muscular work performed pedaling on bicycle. The energy level was determined by performing metered loads with changing facilities for closed cycle. The data characterizing the physiological "cost" of adaptation, the level of stress the body of students in different phases of muscular work. Developed and presented model characteristics of the energy level of the body of girls. Reviewed degree of mobilization of functional reserves under load for closed loop five-point scale. Defined physical condition of students during the first year. The recommendations of the evaluation and prediction of the actual state of the physical health of students and improve physical education in high school.